Deadlock - Akinyemi, Rowena (Oxford bookworms library, 2000)
"V.I. Warshawski, private investigator, Chicago, USA. People imagine private detectives to be tired-looking men in raincoatd, but Vic is female. She's tough, beautiful, carries a gun -and goes on asking questions until she gets answers. When her cousin Boom Boom dies in an accident, Vic is naturally upset. She wants to know how and why the accident happened, and she isn't satisfied by the answers she gets. So she goes on asking questions ... and more people start to die." --contratapa.